Transparency of information in internal quality procedures in higher education - Revenko , Olena; Revenko, Tetyana (Theory and Practice of Public Administration, 2019)
The education system is constantly reforming, acquiring qualitatively new properties, self-renewing basing on its own principles. Many years of experience in formation the Ukrainian statehood testify that one of the organizational guarantees for forming partnerships is ensuring transparency and openness to the population of administrative processes, activities of government bodies, educational institutions, etc. The main provisions and conditions for ensuring transparency in the internal quality assurance procedures of higher education are: - forming a coherent and consistent system of quality assurance at the macro and micro levels; - compliance with the principle of transparency and openness of information in the available quality assurance procedures; - the dynamism of the educational quality assurance system at the level of institutions; - adherence to the policy of transparency in all directions of activity of the institution; - creation (if it exists already, so improvement) of personal educational systems, - strengthening of autonomy of higher education institutions activity and public relations in both strategic and tactical plane; - developing its own methodology for assessing transparency and openness of information for internal use, etc. Thus, nowadays, information openness is important in the context of forming a new type of relationship and management style, which in turn is reflected in the image of higher education institutions in general, and therefore its activity in the introductory campaigns.